The Factor Model of the Solitude Emotional Experience - Oleynik, Narmina (Psychological Prospects Journal, 2016)
The article focuses on the investigation of solitude phenomenon. The difficulties in defining solitude and interpretation of the solitude emotional experience essence are explained by a certain contrariety in the theoretical understanding of solitude as a mental phenomenon. It is determined that solitude evinces not only in the negative aspect of personality development. Solitude can often serve as an indispensable condition of personality self-perfection. Indisputably solitude may be accompanied by typical negative emotions, feelings and states, and yet people just need to find new or strengthen old points of internal resistance in certain situations, to refocus, to rebuild the system of meaningful goals, to switch to the other areas of self-actualization (eg, creative work, professional status change). In this context the term “solitude” is regarded as a category of emotional experience. Based on the systematic approach principles and categorial apparatus, solitude is regarded as a unitary, integral system, the integrity of which is ensured by the fact that the emotional experience of solitude operates through interaction of such components as cognitive (provides the functions of solitude emotional experience idea and perception of oneself as a subject; consists of such mechanisms as identification and separation), emotional (provides emotional evaluation functions and peculiarities of own feelings acceptance-rejection), behavioral (provides actions on certain emotional experiences; it is realized in such mechanisms as isolation, alienation and solitude), motivational and volitional (complex of motives and voluntary actions concerning emotional experience; consists of such mechanisms as self-actualization and depersonalization). Based on the theoretical model of solitude emotional experience, the factor analysis aimed on marking out the minimum number of generalized factors that reflect the most significant characteristics of the investigated object was conducted. Key words: loneliness, isolation, alienation, solitude, dissociated, self-actualization.